2014
DOI: 10.1186/ar4522
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated and increased joint damage in young mice with global inactivation of mitogen-inducible gene 6 after ligament and meniscus injury

Abstract: IntroductionLigament and meniscal damage can cause joint disease. Arthritic joints contain increased amounts of epidermal growth factor receptor (EGFR) protein, and polymorphisms in EGFR are associated with arthritis risk. The role of endogenous EGFR regulation during joint disease due to ligament and meniscal trauma is unknown. Mitogen-inducible gene 6 (MIG-6) can reduce EGFR phosphorylation and downstream signaling. We examined the effect of EGFR modulation by MIG-6 on joint disease development after ligamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…RNA sequencing analysis revealed that 33 genes were enriched in anti-Flag samples compared with anti-IgG samples (Supplementary Table S2). Among those targets, we found that two genes, Mig6 [35, 36] and Tnfrsf12a [40, 41], had been reported to be involved in the regulation of bone development (Figure 5b and Supplementary Table S2). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RNA sequencing analysis revealed that 33 genes were enriched in anti-Flag samples compared with anti-IgG samples (Supplementary Table S2). Among those targets, we found that two genes, Mig6 [35, 36] and Tnfrsf12a [40, 41], had been reported to be involved in the regulation of bone development (Figure 5b and Supplementary Table S2). …”
Section: Resultsmentioning
confidence: 99%
“…Given that Samd4-deficient mice exhibited osteopenic phenotype and that Mig6-deficient mice displayed a subchondral bone phenotype [35, 36], we hypothesized that SAMD4 may regulate Mig6 by binding and inhibiting the translation of Mig6 mRNA. Indeed, upregulating the expression of SAMD4 resulted in a decrease in MIG6 protein level (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first study to implicate Mig-6 in OA described OA-like pathology with cartilage degeneration, osteophyte formation, and subchondral cysts in mice harboring global Mig-6 deletion [70]. Further studies aimed to elucidate the tissue-specific role of Mig-6 within the joint and identified similar joint pathologies, in addition to aberrant proliferative activity in both the cartilage and joint periphery [71][72][73][74]. These data indicate a much more complex role of Mig-6, and possibly EGFR signaling, in joint homeostasis.…”
Section: The Other Guysmentioning
confidence: 96%